2013
DOI: 10.1007/s00737-013-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of paternal perinatal depressiveness and its link to partnership satisfaction and birth concerns

Abstract: Depressive disorders have shown an increasing prevalence over the past decades. Growing evidence suggests that pregnancy and childbirth trigger depressive symptoms not only in women but likewise in men. This study estimates the prevalence of paternal perinatal depressiveness in a German community sample and explores its link to partnership satisfaction as well as birth-related concerns and concerns about the future. Data was gathered in a longitudinal study over the second and third trimester of their partner’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 39 publications
6
66
2
2
Order By: Relevance
“…Depressive symptoms in the present study were assessed at a single time point in the late second or early third trimester. It has been suggested that paternal depressive symptoms may fluctuate over the course of pregnancy (Figueiredo & Conde, 2011;Gawlik et al, 2014;Teixeira et al, 2009), similar to what has been observed for maternal antenatal depressive symptoms (Matthey & Ross-Hamid, 2012). In the final models 29% to 32% of the variance in antenatal paternal depressive symptoms was explained, suggesting that other variables not assessed in this study (i.e., history of depression, pregnancy and birth related anxiety, prior perinatal loss, trauma history) require further study to determinate their relative contributions.…”
Section: Discussionsupporting
confidence: 71%
“…Depressive symptoms in the present study were assessed at a single time point in the late second or early third trimester. It has been suggested that paternal depressive symptoms may fluctuate over the course of pregnancy (Figueiredo & Conde, 2011;Gawlik et al, 2014;Teixeira et al, 2009), similar to what has been observed for maternal antenatal depressive symptoms (Matthey & Ross-Hamid, 2012). In the final models 29% to 32% of the variance in antenatal paternal depressive symptoms was explained, suggesting that other variables not assessed in this study (i.e., history of depression, pregnancy and birth related anxiety, prior perinatal loss, trauma history) require further study to determinate their relative contributions.…”
Section: Discussionsupporting
confidence: 71%
“…One of the men spoke of signs of depression. It seems important to note these emotions as there is data indicating that feelings of isolation, sadness, fear and anxiety are central to men who develop depression [45] , and that the paternal depression rate might be increased during pregnancy as is seen in mothers [46] .…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…[105][106][107][108][109][110] New fathers were 1.38 times as likely to be depressed as comparably aged males. 111 A recent study found that nonresident fathers reported higher depression symptoms during the transition to fatherhood, but resident fathers had a 68% increase in their depressive symptoms in the first 5 years of fatherhood.…”
Section: Influence Of Fathers' Mental and Physical Well-being On Chilmentioning
confidence: 99%